The soluble fms-like tyrosin kinase-1 (sFLT-1) to placental growth factor (PIGF) ratio as a possible indicator for the severity of preeclampsia - single institution experience - Andrijana Müller; Vesna Horvat; Martina Vulin; Sanja Mandić; Vatroslav Šerić; Domagoj Vidosavljević (Medicinski glasnik, 2018)
Aim: To investigate a potential of the clinical use of the soluble fms-like tyrosine kinase 1 (sFLT-1) to placental growth factor (PlGF) ratio from the perspective of a small hospital centre. Methods: Maternal serum samples were analysed at 24 1/7-28 0/7 , and 28 1/7-32 0/7 weeks of gestation. The level of sFLT-1 and PIGF was determined by immunoassay platform and used to calculate the sFLT-1/PIGF ratio in 35 pregnant women, and divided into subgroups according to preeclampsia occurrence at the time of delivery: preterm (?37 weeks) or term (37-42 weeks'), and matched a control group. Results: Patients in the preterm delivery group had a significantly higher incidence of intrauterine growth restriction, lower gestational age at the time of delivery, and lower infant birth weight compared to the other two groups. There was a negative correlation between the sFLT-1/PlGF ratio and GA and between the sFLT-1/ PlGF ratio and birth weight at the time of delivery. The value of the sFLT-1/PlGF ratio was significantly higher in the preterm delivery PE group. All the PE group pregnancies ended with caesarean delivery compared to 25% in the control group. However, none of the patients from the PE group had any of the possible complications of preeclampsia nor did they require additional therapy such as blood transfusion or additional non-standard hypertensive therapy. Conclusion: The sFLT-1/PlGF ratio could be used as an indicator for the development and estimation of the severity of PE to provide objective evidence for the management of preeclampsia patients, and as a predictive marker of preeclampsia at low cost.
Keywords: eclampsia; pregnancy complications; placenta; premature birth